Gerenciamento de resíduos sólidos domiciliares no Município de Fortaleza/CE, Brasil - Garcia, Hozana Raquel de Medeiros (2021)
The management of household solid waste (RSD) consists of the stages of collection, transportation, treatment, destination and final disposal, so the purpose of this article was to describe its phases and present the amount of waste that is managed in the city of Fortaleza (CE) in regular, ecopolo, selective and ecopoint collection; transport, transshipment station, recycling and landfill. For that, literary definitions related to the stages of RSD management and secondary data on this management in the studied municipality were presented, showing its functional organization and quantities of waste managed. It was observed in the results that Fortaleza has a diversified collection system, in addition to having a transshipment station, sanitary landfill and recycling industries. It was found that the amount of RSD from regular door-to-door collection and underground dumps (ecopolises) was the largest of the collection systems with a value of 808271.15 tons; followed by ecopoints with 12790 t. debris and recycled materials and selective collection with 6263.6 t. In addition, it was found that transportation is approximately 19 km between transshipment and landfill. The amount of waste managed at the transshipment station was 405596.9 t. in 2017 and to the landfill 1452132.4 t. It was observed that the diversity in the collection of RSD in the city provides a greater efficiency in its management, thus aiming to reduce irregular points of garbage throughout the city.